Developmental and Sexual Offense Onset Characteristics of Australian Indigenous and Non-Indigenous Male Youth Who Sexually Offend. (December 2020) - Adams, Dimity; McKillop, Nadine; Smallbone, Stephen; McGrath, Andrew
The present study sought to address gaps in knowledge concerning Australian Indigenous and non-Indigenous youth who commit sexual offenses. Developmental histories and onset sexual offense characteristics of Indigenous ( n = 81) and non-Indigenous ( n = 130) adjudicated male youth were compared. Results indicate that, in addition to problems affecting both groups, Indigenous youth in this sample were disproportionately exposed to systemic vulnerabilities (e.g., familial antisocial attitudes and incarceration, engagement with antisocial peers, poor school engagement and voluntary school dropout, low socioeconomic status) associated with onset of sexual offending. Differences in the circumstances and context surrounding the onset sexual offense (e.g., use of drugs/alcohol, relationship to person harmed, co-offending, age of person harmed, location, threats/force) were also found. When these analyses were stratified by age of person harmed, these differences were retained only for offenses against children below 16 years. Together, these findings highlight the need for more contextualized primary-, secondary-, and tertiary-level prevention efforts to reduce youth sexual offending in Australia and elsewhere.